Utilizing of Islamic Educational Technology Strategy in Fullfilment Standards of Islamic Education - Muhammad Saidy; Abu Bakar; Rd. Tuti (Educan : Jurnal Pendidikan Islam, 2021)
Education strategies supported by quality human resources (HR) are an important component in the fulfillment of Islamic education standards. IMTAQ  ( Faith and and piety), Science and technology are the two main competencies that determine the quality of human resources in the world of education. Therefore, in the fulfillment of educational standards, the education strategy applied must be designed with the two human resource competencies in mind. However, there are times when, the minister faces some problems in designing strategies oriented to the utilization of science and technology. This research is library research. Analysize some references from journals, books, magazines, and other sources of information. Therefore, this paper aims to discuss how the use of technology can be used as one of the strategies in achieving Islamic education standards. Based on the discussion, it can be concluded that in order to meet islamic education standards, Islamic Aqidah should be used as the basis of all science and technology concepts and applications. In line with that, Islamic Sharia should be used as a standard for the use of science and technology.